Nghiên cứu đặc tính hóa lý của hệ oxit hỗn hợp V-Mg-O - Vũ và cộng sự, Nguyễn Anh (Vietnam Journal of Chemistry, 2014)
Vanadium – Magnesium mixed oxides used for the oxidative dehydrogenation was synthesized by impregnation method. Characterization of catalysts was determined by serial model techniques such as XRD, TPR-H2, TPD-NH3, FT-IR and N2 physisorption. The result of XRD showed that V2O5 phase was inhibited in the V-Mg-O mixed oxides prepared with impregnation method. FT-IR spectra and TPR-H2 profile showed the present of isolated VO4 tetrahedral species in surface mixed oxide, which enhance catalytic activity of ODH reaction.